Review of Aquatic Ecology Problems - Athosra Athosra; Abdul Razak; Eni Kamal; Isril Berd (Pascasarjana, Universitas Negeri Padang, 2022)
Ecology which studies individual organisms is called autecology, the environment is mainly studied in environmental science which is applied ecology with the aim that humans can apply the basic principles and concepts of ecology in the living environment. In ecology, the relationship between living things and their environment is objective, humans are seen as equal to other living things. In environmental science, humans are distinguished from other living things, and the view of the relationship between humans and the environment is subjective (ecology and environmental science). In ecology, interactions are not only between organisms and abiotic components but also between living organisms themselves. Interactions can occur between organisms of the same type or population.